Eksistensi Kurikulum Kolaboratif di Sekolah Dasar Berbasis Islam dalam Upaya Mempersiapkan Mutu Lulusan Unggul - Indra Lesmana; Burhanuddin Burhanuddin; Asep Sunandar (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2024)
Abstract: The curriculum is said to be the main capital that determines the success of learning in each educational unit. Each educational unit has characteristics and characteristics in managing and developingits  curriculum based on the vision, mission, and goals of the   school. The purpose of this study is to describe (1) the implementation of a collaborative curriculum in Islamic-based elementary schools, (2) the impact  of the application of a  collaborative curriculum on the quality of graduates. The research was conducted qualitatively with a multi-site study approach. The research location is at  Baitul Makmur Islamic Elementary School and Al-Rifa'ie Modern Elementary School Malang. Data collection was conducted by semi-structured interviews, observations, and documentation studies. Checking the credibility of data is carried out by means of diligence of observation, triangulation, checking members, and discussion of fellow researchers. The results of this study show that (1) the application of the  collaborative curriculum basically refers to the vision, mission and goals of the school which focuses on preparing the quality of superior graduates in terms of academics, skills, and character. (2) The impact of implementing a  collaborative curriculum is that students when graduating from school have advantages including good morals and religion. Students are more skilled in English  and Irab and can read,   write, and even memorize the Qur'an and hadith. Students are also able to make achievements from various competition events at the subdistrict, city, and provincial levels.Keywords: Collaborative Curriculum, Learning, Curriculum Developer, Islamic School, Excellent graduate quality Abstrak: Kurikulum dikatakan sebagai modal utama yang menentukan keberhasilan pembelajaran di setiap satuan pendidikan. Setiap satuan pendidikan memiliki karakteristik dan ciri khas dalam mengelolah dan mengembangkan kurikulumnya didasarkan atas visi, misi, dan tujuan sekolah. Tujuan penelitian ini untuk mendeskripsikan mengenai (1) penerapan kurikulum kolaboratif di sekolah dasar berbasis Islam, (2) dampak penerapan kurikulum kolaboratif terhadap mutu lulusan. Penelitian dilakukan secara kualitatif dengan pendekatan studi multi situs. Lokasi penelitian di Sekolah Dasar (SD) Islam Baitul Makmur dan SD Modern Al-Rifa’ie Malang. Pengumpulan data dilakukan dengan wawancara semi terstruktur, observasi, dan studi dokumentasi. Pengecekkan kredibilitas data dilakukan dengan cara ketekunan pengamatan, triangulasi, pengecekan anggota, dan diskusi teman sesama peneliti. Hasil penelitian ini menunjukan bahwa (1) penerapan kurikulum kolaboratif pada dasarnya mengacu pada visi, misi dan tujuan sekolah yang memfokuskan untuk mempersiapkan mutu lulusan unggul dari segi akademik, keterampilan, dan karakter. (2) dampak penerapan kurikulum kolaboratif adalah peserta didik ketika lulus dari sekolah memilki keunggulan diantaranya berakhlak baik dan religius. Peserta didik lebih terampil berbahasa Inggris dan Arab serta dapat membaca, menulis, bahkan menghafal Al-Qur’an dan hadis. Peserta didik juga mampu menorehkan prestasi dari berbagai event perlombaan baik tingkat kecamatan, kota, maupun provinsi.Kata kunci: Kurikulum Kolaboratif, Pembelajaran, Pengembang Kurikulum, Sekolah Islam, Mutu Lulusan Unggul